SPEECH AND SELF-IDENTIFICATION: (Management and Connections Journal, 2021)
The problem with this study is how the history of self-identification in the Luizes community can be constructed from the memory of its members. The work was done through the quilombo Luizes' old narratives in unstructured interviews. The stories and memories showed some findings, among which: i) the Luizes Community's self-identification discourse is marked by positive recognition of the term, but not by all people in the community, which indicates that homogeneity is not a condition for the existence of an organization, ii) quilombola self-identification is a discourse crossed by several others, which exert tensions and disputes around the meaning, iii) the contradictions observed do not relate to the incoherence of its members, but are linked to a constituted society in structural racism that led to the invisibility of stories and the erasure of humanities.